(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The contributions made by different people and organizations to the Maharashtra independence movement during the British Raj are examined in this study. It looks at the actions of well-known people, including the Chapekar brothers, Bal Gangadhar Tilak, and Vasudev Balwant Phadke, emphasizing their use of armed resistance and acts of defiance. The article delves into the involvement of groups like Abhinav Bharat and Arya Samaj in revolutionary operations, as well as the difficulties they encountered. The study also highlights the efforts made by lesser-known heroes like Anant Laxman Kanhere, Babu Genu, and Babu Shedmake to the greater freedom movement, and respects their sacrifices.